TINJAUAN KELENGKAPAN INFORMASI PENUNJANG MEDIS PASIEN RAWAT JALAN DI RUMAH SAKIT TNI-AD BHIRAWA BHAKTI KOTA MALANG - Sita Dwi Fahyanti; Chyntia Vicky Alvionita; Avid Wijaya (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2022)
The completeness of medical supporting information for outpatients at the TNI-AD Bhirawa Bhakti Hospital, Malang City, was still found to be incomplete, which affected the filling out of forms in medical record documents. In the research, it was discovered that 19 documents had a percentage of 21% (incomplete) and 71 documents had a percentage of 79% (complete). The aim of this research is to analyze the completeness of medical supporting information for outpatients at the Bhirawa Bhakti TNI-AD Hospital, Malang City. This type of research uses quantitative data collection in the form of observations and interviews, while the research instrument uses a checklist sheet. The number of samples used was 90 medical records from April-June 2023 for outpatients. In this study, the average completeness of patient identification results was 80 (88.8%), the average component of important reports was 70 (77.7%), the average component of good records was 66 (73.3%) , and the authentication review component was 69 (76.6%). From the 4 components, the total results of the recapitulation of completeness of medical supporting information obtained a complete total of 71 (79%). Conclusion: factors that influence incompleteness in medical record documents are incompleteness in the Dpjp's signature, the Dpjp's name, and the readability of the doctor's writing which is less understandable.